A New Paradigm for Social License as a Path to Marine Sustainability - Uffman-Kirsch, Lisa B.; Richardson, Benjamin J.; van Putten, Elizabeth Ingrid (Frontiers in Marine Science, 2020)
Traditional marine governance can create inferior results. Management decisions customarily reflect fluctuating political priorities and formidable special-interest influence. Governments face distrust and conflicts of interest. Industries face fluctuating or confusing rules. Communities feel disenfranchised to affect change. The marine environment exhibits the impacts. While perceived harm to diverse values and priorities, disputed facts and legal questions create conflict, informed and empowered public engagement prepares governments to forge socially legitimate and environmentally acceptable decisions. Integrity, transparency and inclusiveness matter. This paper examines positive contributions engaged communities can make to marine governance and relates it to social license. Social license suffers critique as vague and manufactured. Here its traditional understanding as extra-legal approval that communities give to resource choices is broadened to include a legally-sanctioned power to deliberate—social license to engage. The starting hypothesis rests in the legal tradition designating oceans as public assets for which governments hold fiduciary duties of sustainable management benefitting current and future generations. The public trust doctrine houses this legal custom. A procedural due process right for engaged communities should stem from this public-asset classification and afford marine stakeholders standing to ensure management policy accords with doctrinal principles. The (Free), Prior, Informed Consent participation standard provides best practice for engaged decision-making. Building on theories from law, social and political science, we suggest robust public deliberation provides marine use actors methods to earn and sustain their social license to operate, while governmental legitimacy is bolstered by assuring public engagement opportunities are available and protected with outcomes utilized.